P-101 Advance care planning: A systematic review of randomised controlled trials conducted with older adults. (1st September 2015) - Weathers, Elisabeth; Cornally, N; Coffey, Alice; Daly, Edel; Molloy, D William
Abstract : Background: Several randomised controlled trials have tested the effects of advance care planning (ACP) interventions on a range of different outcomes. There is a need to synthesise and analyse these findings to identify gaps in knowledge and make recommendations for further research. Aim: The aim of this study was to systematically review the effectiveness of ACP interventions implemented with older adults (>65 years old). Methods: A systematic review of the literature was conducted using the CINAHL, PubMed and Cochrane databases from the earliest available date through to September 2014. Results: Of the 220 abstracts identified, nine met the inclusion criteria. These studies consisted of a sample of 3, 646 older adults (age range 72–88 years). The majority of studies were conducted in the USA (n = 6). Types of ACP interventions, and outcomes measured, varied considerably making it difficult to synthesise the findings. Only two studies were conducted in nursing homes. Most studies did not implement a standardised advance care directive, or measure the impact of interventions on quality of end-of-life care, or on quality of the death and dying experience. Only three studies scored 3 on the Oxford Quality Scale and all had some risk of bias according to the Cochrane Effective Practice and Organisation of Care criteria. Conclusion: Further research is needed to assess the impact of ACP interventions on quality of care and on quality of the death and dying experience, particularly in nursing home settings. Future studies should also take into account the economic impact (costs vs benefits).